CONSEQUENCES OF PHYSICAL ACTIVITY FOR THE ELDERLY HEALTH (Fiep Bulletin - online, 2014)
Abstract: The Extension Project named Body Workshop is part of the Interdisciplinary Pole in the Sector on Ageing Issues of the Federal University of Juiz de Fora (Universidade Federal de Juiz de Fora). It focuses on work with motor activities both through Movement and Expression. In 2006, a research was conducted and, in it, 30 people over sixty years old were interviewed. It was aimed at investigating what the meaning of "being elderly nowadays" is and "how they felt in relation to the practice of physical activities." The conclusions pointed out to the fact that people in this age group identify, firstly, the negative points of ageing in relation to the following aspects: physical (grey hair, wrinkles); biological (diseases, difficulty to move about and tiredness); psychological (impatience, sadness and lack of affection). After this, they identify the positive aspects, which appeared related to both experience and wisdom. It should be pointed out that, after the practice of physical activities for at least a year, these people reported improvements, such as disposition to daily activities, a higher self-esteem and more joy of living However, what has drawn the researchers' attention were the ambiguities and controversies in the answers, once they demonstrated some difficulty in naturally accepting, the ageing process as an irrefutable phase of life.
Keywords: elderly; ageing; physical activities; health